VALIDITY OF ETHNOSCIENCE-BASED TEXTBOOK ON ENVIRONMENTAL CHANGE TOPIC TO INFLUENCE ENVIRONMENTAL LITERACY SKILL OF 10th GRADE HIGH SCHOOL STUDENTS - Ianatur Rofiqoh; Ulfi Faizah (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2019)
Abstract Environmental Change topic can be taught by integrating ethnoscience in learning proccess, because it can produce more meaningful learning, such as to influence students’ environmentally literacy skills. One way to integrate ethnoscience in learning is through textbooks. The purpose of this research was to describe the validity of ethnoscience-based textbook on environmental change topic to influence environmental literacy skill of 10th grade high school students. The development of this ethnoscience-based textbook was held in Biology Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya. This research used 4-D developmental model (Define, Design, Develop, and Disseminate), however this research was done until develop stage. Data collected by validation method and validity sheet as it instrument. The data then analyzed by descriptive technique. Result showed that ethnoscience-based textbook had special characteristics that were presented in the features of the study of ethnoscience, environmental literacy features, and other supporting features. Based on the validity result, which included the feasibility of presentation, graphics, content, and language by experts, these ethnoscience-based textbook gained a score with mode of 4 and a very feasible category mode. Thus, ethnoscience-based textbook was very feasible and can be applied in biology learning.   Keyword : validity, ethnoscience, textbook, environmental topic